Three-Dimensional High-Definition Neuroendoscopic Surgery: A Controlled Comparative Laboratory Study with Two-Dimensional Endoscopy and Clinical Application - Inoue, Daisuke; Yoshimoto, Koji; Uemura, Munenori; Yoshida, Masaki; Ohuchida, Kenoki; Kenmotsu, Hajime; Tomikawa, Morimasa; Sasaki, Tomio; Hashizume, Makoto (Journal of Neurological Surgery Part A: Central European Neurosurgery, 2013)
Background The purpose of this research was to investigate the usefulness of three-dimensional (3D) endoscopy compared with two-dimensional (2D) endoscopy in neuroendoscopic surgeries in a comparative study and to test the clinical applications.Methods Forty-three examinees were divided into three groups according to their endoscopic experience: novice, beginner, or expert. Examinees performed three separate tasks using 3D and 2D endoscopy. A recently developed 3D high-definition (HD) neuroendoscope, 4.7 mm in diameter (Shinko Optical Co., Ltd., Tokyo, Japan) was used. In one of the three tasks, we developed a full-sized skull model of acrylic-based plastic using a 3D printer and a patient's thin slice computed tomography data, and evaluated the execution time and total path length of the tip of the pointer using an optical tracking system. Sixteen patients underwent endoscopic transnasal transsphenoidal pituitary surgery using both 3D and 2D endoscopy.Results Horizontal motion was evaluated using task 1, and anteroposterior motion was evaluated with task 3. Execution time and total path length in task 3 using the 3D system in both novice and beginner groups were significantly shorter than with the 2D system (p < 0.05), although no significant difference between 2D and 3D systems in task 1 was seen. In both the novice and beginner groups, the 3D system was better for depth perception than horizontal motion. No difference was seen in the expert group in this regard. The 3D HD endoscope was used for the pituitary surgery and was found very useful to identify the spatial relationship of carotid arteries and bony structures.Conclusions The use of a 3D neuroendoscope improved depth perception and task performance. Our results suggest that 3D endoscopes could shorten the learning curve of young neurosurgeons and play an important role in both general surgery and neurosurgery.
Keywords: three-dimensional high-definition endoscope; neuroendoscopic surgery; transsphenoidal surgery; laboratory investigation; depth perception